1983
DOI: 10.1159/000198955
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Gastroparesis: Treatment with Domperidone -A Double-Blind, Placebo-Controlled Trial

Abstract: 6 patients with severe symptomatic diabetic gastroparesis were studied in a placebo-controlled randomized manner to establish if intravenous domperidone accelerates the delayed gastric emptying of a semisolid homogenized meal. Domperidone, 10 mg intravenously, shortened the gastric emptying half-time in all of the 6 patients significantly, but not in the healthy control subjects. These results suggest that intravenous domperidone may be potentially beneficial to diabetic gastroparesis patients by improving del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 7 publications
(9 reference statements)
2
20
0
Order By: Relevance
“…Previous studies have shown no correlation between improvement in gastric emptying and GI symptoms with the use of prokinetics but this recent review cited study limitations that included the use of a variety of drugs, doses, lengths of treatments, and a limited number of studies available . Multiple open‐label and randomized controlled studies in adults have shown an improvement in symptom intensity when comparing domperidone to placebo . See Table for available studies.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Previous studies have shown no correlation between improvement in gastric emptying and GI symptoms with the use of prokinetics but this recent review cited study limitations that included the use of a variety of drugs, doses, lengths of treatments, and a limited number of studies available . Multiple open‐label and randomized controlled studies in adults have shown an improvement in symptom intensity when comparing domperidone to placebo . See Table for available studies.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Cisapride, an acetylcholine-releasing agent, is efficacious and is used widely in patients with such GI conditions as gastroesophageal reflux disease and non-ulcer or functional dyspepsia; but patients with symptoms of diabetic gastroparesis may benefit from the combined prokinetic and antiemetic effects of dopamine antagonists, such as domperidone and metoclopramide. Domperidone, a new dopamine antagonist with predominant peripheral antagonism, is also effective for the treatment of dyspepsia and symptoms of diabetic gastroparesis (4)(5)(6)(7)(8)(9)(10)(11). Unlike metoclopramide, domperidone does not readily cross the blood-brain barrier and is therefore less likely to cause undesirable central nervous system effects, such as drowsiness, restlessness, anxiety, and fatigue (12).…”
mentioning
confidence: 99%
“…Because domperidone does not penetrate into the central nervous system, its effects are confined to the periphery. An acute double-blind placebo-controlled trial showed that 10 mg domperidone i. v. enhanced the emptying of a semi-solid meal in all of six diabetic patients with symptomatic gastroparesis but had no effect in six healthy subjects [148]. In a double-blind study in 12 Type I diabetic patients with cardiovascular ANP, a single oral dose of 40 mg domperidone accelerated the emptying of both solids and liquids significantly more than placebo did [149].…”
Section: Treatments Aimed At Accelerating Gastric Emptyingmentioning
confidence: 98%